Feasibility and Acceptability of a Clinic-based Mediterranean-style Diet Intervention to Reduce Cardiovascular Risk for Hispanic Americans With Type 2 Diabetes. (June 2017) - Cubillos, Laura; Estrada del Campo, Yanire; Harbi, Khalil; Keyserling, Thomas; Samuel-Hodge, Carmen; Reuland, Daniel S.
Purpose: The purpose of the study was to modify a previously tested Spanish language version of a Mediterranean (Med)-style dietary intervention so that the dietary recommendations align with the cultural and social needs of Hispanic Americans (HAs) with type 2 diabetes (T2D) and evaluate the modified intervention's feasibility and acceptability. Methods: In phase I (formative), semi-structured interviews and focus groups were used to refine the intervention content and format for delivery to HAs with T2D receiving care at a large primary care practice. In phase II (clinical pilot), the 2-month intervention that promoted a Med-style dietary pattern was given to all participants via 2 face-to-face counseling sessions and 2 telephone counseling sessions. Major outcomes were engagement with study activities and intervention acceptability; dietary behavior change at 2 months using the PREDIMED Med-diet score (range, 0-14, higher indicating better dietary pattern) is also reported. Results: From clinic records, we identified 86 potentially eligible participants and enrolled 21. Baseline characteristics were: mean age = 52 years, 12 (57%) female, 15 (71%) from Mexico, mean years in the US = 19, low acculturation scores for all, and mean BMI = 33.7 kg/m 2 . Engagement and acceptability were high, with 19 (90%) completing all intervention visits and follow-up measures, all of whom would recommend the program to others. Mean Med-diet score improved from 5.7 to 7.9 (difference = 2.3; 95% CI, 1.0-3.5; P = .001). Conclusions: Intervention engagement and acceptability were high, and there was improvement in self-reported dietary behaviors. This type of intervention should be evaluated in randomized trials enrolling HAs with diabetes.